Поселення Павлівка ІІ поблизу Комсомольська - Шерстюк, В.В.; Лямкін, В.В. (Археологічні дослідження в Україні, 2009)
The paper contains a description of the inspection results at the Bronze Age and Ancient Rus period settlement Pavlivka II in the mouth of the Sukhyi Kobelyachok River, of some finds in destroyed cultural layers, as well as of a Bilozerska culture burial studied in the washed areas.